The Effect of Lavender Aromatherapy Scores in Mothers with Postpartum Blues - Anggraini Anggraini; Neneng Siti latifah; Desmalia Desmalia (Poltekkes Kemenkes Palu, 2026)
Introduction: Postpartum blues is a mild mood disorder that commonly occurs in postpartum mothers, characterized by mood swings, anxiety, and emotional exhaustion. Globally, the incidence of postpartum blues is affects about 50-80% of mothers after giving birth, while in Indonesia the prevalence reaches 50-70%, If not properly managed, this condition may develop into more severe postpartum depression, which can negatively affect the mother–child relationship and overall family well-being. This study aims to determine the effect of lavender aromatherapy on EPDS scores in mothers with postpartum blues in the Working Area of UPTD Madukoro Primary Health Care, North Lampung Regency Methods: This study used quantitative methods with a quasi experiment design and pretest-posttest design with control group. The study population consisted of all postpartum mothers on the third day who experienced postpartum blues, with a sample of 30 participants divided into 15 in the intervention group and 15 in the control group. Results: The results showed that the average EPDS score in the group given lavender aromatherapy decreased from 11.87 to 3.6. In the control group, it decreased from 11.53 to 5.27. The greater decrease in the intervention group showed a significant effect of lavender aromatherapy on reducing EPDS scores in mothers with postpartum blues with a p-value of 0.000. Conclusion: lavender aromatherapy has a significant effect on reducing EPDS scores in mothers with postpartum blues.